Captopril in renovascular hypertension: long-term use in predicting surgical outcome. Issue 6317 (6th March 1982) - Atkinson, A B; Brown, J J; Cumming, A M; Fraser, R; Lever, A F; Leckie, B J; Morton, J J; Robertson, J I
Abstract : The angiotensin converting-enzyme inhibitor captopril was used as long-term preoperative treatment in a series of hypertensive patients with unilateral renal arterial disease. There were immediate and sustained falls in plasma angiotensin II and aldosterone concentrations, with converse increases in circulating renin and angiotensin I. In patients with sodium and potassium deficiency and secondary aldosterone excess before treatment captopril corrected the sodium and potassium deficits; in these cases the initial hypotensive response was profound but the later effect was less pronounced. When sodium and potassium state was initially normal it remained unchanged during captopril treatment, while the full hypotensive effect took up to three weeks to be attained. The immediate, but not long-term, falls in arterial pressure with captopril were proportional to the immediate decrements of plasma angiotensin II. Nevertheless, while the immediate blood-pressure reduction with captopril variously overestimated and underestimated the eventual surgical response, the absolute blood-pressure values during long-term captopril related well with those after operation. Pretreatment plasma renin and angiotensin II concentrations, while closely predicting the immediate captopril response, are fallible guides to surgical prognosis. In contrast, long-term treatment with converting-enzyme inhibitors may provide an accurate indication of surgical outcome.